Arabic–English Pocket Dictionary (Cory) Based on Symbolic Art to Increase Arabic Vocabulary Mastery in Elementary School - Kiki Safitri; Nurhidayati; Hanik Mahliatussikah; Pabiyah Toklubok@Hajimaming (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to describe the Arabic–English Pocket Dictionary (Cory) Based on Symbolic Art to increase Arabic vocabulary mastery in elementary school. To find out how Cory is implemented and increased, this research uses classroom action research methods. Classroom action research (CAR) is a research method whose implementation is carried out to find out problems in the learning process as well as steps that teachers can take to improve the quality of learning, which refers to the research implementation process, consisting of four stages, namely (1) Planning, (2) Actualing, (3) Observation, and (4) Reflecting (reflecting in general on the research process). This must be done in at least two cycles if it shows the target that has been determined. The research process was carried out in two cycles. The results of the first and second cycle post-tests obtained an average score of 76 and 95, respectively, with learning completeness results in each cycle of 70% and 100%. Thus, the percentage increase in student learning outcomes is 30%.